PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN - Bachrudin, Burhan; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of the research is to examine and to analyze the influence firm size to the firm value, theinfluence of leverage to the firm value, and the influence of managerial ownership to the firm value. Firm value isproxy by the PBV. The population is consumer goods industrial sector manufacturing companies particularly inthe field of pharmacy which are listed in Indonesia Stock Exchange (IDX) in 2012-2014 periods. The sampleselection has been carried out by using purposive sampling and certain criteria so 10 manufacturing companieswith 30 observations have been obtained. The data analysis method has been carried out by using multiple linearregressions analysis and the SPSS (Statistical Product and Service Solutions). Based on the result of theresearch, it shows a problem that leverage has significant and negative influence to the firm value with itsregression coefficient -4.113 and significance level 0.021, whereas firm size and managerial ownership does nothave any significant influence to the firm value. Simulatenously, independent variables have signfinicantinfluence to the dependent variables with its significance level 0.020.Keywords: Firm size, leverage, managerial ownership, firm value